Docosahexaenoic acid promotes differentiation of photoreceptor cells in three-dimensional neural retinas. (October 2017) - Arai, Eisuke; Parmar, Vipul M.; Sahu, Bhubanananda; Perusek, Lindsay; Parmar, Tanu; Maeda, Akiko
Highlights: Docosahexaenoic acid (DHA) supplementation leads to photoreceptor maturation in vitro . An efficient culture method to develop retinal tissues with photoreceptor layer. Culture with 9- cis -retinal does not benefit photoreceptor development. Abstract: Retinal tissues generated from human pluripotent stem cells can be an excellent tool for investigating pathogenesis of retinal diseases and developing new pharmacologic therapies. Moreover, patient derived retinal tissues could allow for retinal transplantation therapy for degenerative retinal diseases. However, obtaining retinal tissues with matured photoreceptor outer segments, which are essential for photoreceptor functions, is currently challenging. Here we investigated the effects of docosahexaenoic acid (DHA) for maturation of photoreceptor outer segments at the late stage and visual chromophore analog, 9- cis -retinal for the early stage of differentiation to three-dimensional (3D)-retinal tissues from human embryonic stem cells (hESCs), respectively. In the presence of DHA, differentiated 3D-retinal tissues demonstrated improved maturation of photoreceptor outer segments and increased number of photoreceptor cells compared with tissues without DHA. Increased mRNA expression of mature photoreceptor markers was additionally documented in retinal tissues cultured with DHA. Conversely supplementation with 9- cis -retinal failed to improve differentiation of retinal tissues perhaps due to chronic aldehyde toxicity. The current study demonstrated that the addition of DHA to culture medium can help promote differentiation of photoreceptor outer segments in vitro and utilization of this methodology may lead to future therapies for patients with blinding diseases.